Kelalaian Pencatatan Nikah Pada Perkawinan di Bawah Umur di Kabupaten Gorontalo - Yunus I. M. Umar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
Marriage registration is important in marriages in Indonesia because it can have legal consequences for those who carry out marriages. This study discusses the form of negligence of marriage registration in underage marriages in Gorontalo District and the legal consequences that occur due to negligence of marriage registration in age marriages in Gorontalo Regency. This research is a field research with a juridical and sociological approach. The collection of data in the form of observations at the study site, interviews with employees of the Office of Religious Affairs, parents and underage marriages with 182 respondents, as well as literature review. The results showed: First, the form of negligence in the registration of marriages in Gorontalo Regency, namely the negligence of parents, the negligence of children and the negligence of marriage registration officers; Second, due to the legal consequences caused by negligence in registering underage marriages in Gorontalo District, namely the legality of child marriages, divorce is easy, rejection of marriage dispensation, repeating the marriage contract and marriage without the presence of government officials.